2005
DOI: 10.1080/09548980500463347
|View full text |Cite
|
Sign up to set email alerts
|

Contextual modulation of orientation tuning contributes to efficient processing of natural stimuli

Abstract: It has been proposed that sensory neurons are adapted to the statistical structure of the natural environment in order to encode natural stimuli efficiently. While spatiotemporal correlations in luminance signals may be decorrelated by neurons in early visual processing stages, higher-order correlations, such as those in the orientation domain, are likely to persist in the input representation until the cortical level. In this study, we first examine orientation correlations in natural stimuli across brief tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 34 publications
6
54
1
Order By: Relevance
“…3A). Similar changes in gain have been reported in macaque V1 (Müller et al, 1999;Wissig and Kohn, 2012;Patterson et al, 2013) and in cat V1 (Dragoi et al, 2000(Dragoi et al, , 2001Felsen et al, 2002Felsen et al, , 2005Benucci et al, 2013). The orientation-tuned reduction in gain largely (but incompletely) compensated for the imbalance in mean responses evoked by a biased stimulus distribution (Fig.…”
Section: Scaling and Shifting Tuning Curvessupporting
confidence: 62%
See 2 more Smart Citations
“…3A). Similar changes in gain have been reported in macaque V1 (Müller et al, 1999;Wissig and Kohn, 2012;Patterson et al, 2013) and in cat V1 (Dragoi et al, 2000(Dragoi et al, , 2001Felsen et al, 2002Felsen et al, , 2005Benucci et al, 2013). The orientation-tuned reduction in gain largely (but incompletely) compensated for the imbalance in mean responses evoked by a biased stimulus distribution (Fig.…”
Section: Scaling and Shifting Tuning Curvessupporting
confidence: 62%
“…In primary visual cortex, prolonged viewing of an oriented stimulus (the adapter) results in response suppression for neurons tuned near the adapter and a repulsive shift of orientation tuning curves away from the adapter (Müller et al, 1999;Dragoi et al, 2000Dragoi et al, , 2001Felsen et al, 2002;Benucci et al, 2013). A standard view of adaptation is that it represents a simple fatigue-like process in highly responsive neurons (i.e., in which adaptation only adjusts the gain of individual neurons according to their recent history of responses) (Maffei et al, 1973;Carandini and Ferster, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this itself runs into other problems, such as being silent about the marked similarity between the effects of temporal context (as in the tilt aftereffect) and spatial context (as in the tilt illusion) (Felsen et al, 2005;Schwartz et al, 2007). Of course, the latter has yet to be shown to operate across levels.…”
Section: Computational Implicationsmentioning
confidence: 99%
“…However, other studies have suggested that neurons along the visual pathway encode complex properties of natural scenes (Simoncelli and Olshausen, 2001;Felsen et al, 2005b). Additional studies showed that natural stimuli elicit complex neural modulations (either facilitation or suppression) originating from within the classical receptive field or its surroundings (David et al, 2004;Felsen et al, 2005a). To better understand the neural encoding of natural stimuli we simultaneously recorded neural populations' response from thousands of points spread over V1.…”
Section: Introductionmentioning
confidence: 99%